Whole genome SNP genotyping and exome sequencing reveal novel genetic variants and putative causative genes in congenital hyperinsulinism. - Maria Carla Proverbio (Public Library of Science (PLoS), 2013)
Congenital hyperinsulinism of infancy (CHI) is a rare disorder characterized by severe hypoglycemia due to inappropriate insulin secretion. The genetic causes of CHI have been found in genes regulating insulin secretion from pancreatic β-cells; recessive inactivating mutations in the ABCC8 and KCNJ11 genes represent the most common events. Despite the advances in understanding the molecular pathogenesis of CHI, specific genetic determinants in about 50 % of the CHI patients remain unknown, suggesting additional locus heterogeneity. In order to search for novel loci contributing to the pathogenesis of CHI, we combined a family-based association study, using the transmission disequilibrium test on 17 CHI patients lacking mutations in ABCC8/KCNJ11, with a whole-exome sequencing analysis performed on 10 probands. This strategy allowed the identification of the potential causative mutations in genes implicated in the regulation of insulin secretion such as transmembrane proteins (CACNA1A, KCNH6, KCNJ10, NOTCH2, RYR3, SCN8A, TRPV3, TRPC5), cytosolic (ACACB, CAMK2D, CDKAL1, GNAS, NOS2, PDE4C, PIK3R3) and mitochondrial enzymes (PC, SLC24A6), and in four genes (CSMD1, SLC37A3, SULF1, TLL1) suggested by TDT family-based association study. Moreover, the exome-sequencing approach resulted to be an efficient diagnostic tool for CHI, allowing the identification of mutations in three causative CHI genes (ABCC8, GLUD1, and HNF1A) in four out of 10 patients. Overall, the present study should be considered as a starting point to design further investigations: our results might indeed contribute to meta-analysis studies, aimed at the identification/confirmation of novel causative or modifier genes.